2001
DOI: 10.1074/jbc.m104855200
|View full text |Cite
|
Sign up to set email alerts
|

Multimerization of Phosphorylated and Non-phosphorylated ArcA Is Necessary for the Response Regulator Function of the Arc Two-component Signal Transduction System

Abstract: To adapt to anaerobic conditions, Escherichia coli operates the Arc two-component signal transduction system, consisting of a sensor kinase, ArcB, and a response regulator, ArcA. ArcA is converted to the active form, phosphorylated ArcA (ArcA-P), by ArcB-mediated phosphorylation. The active ArcA-P binds to the promoter regions of target genes, thereby regulating their transcriptional activities. The phosphoryl group of ArcA-P is unstable with a half-life of 30 min. However, we were able to inhibit the dephosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 24 publications
9
64
0
Order By: Relevance
“…Both phosphorylated, as well as nonphosphorylated ArcA protein bound to this rpoSp1 promoter fragment, but produced different band-shift patterns (Fig. 3A), consistent with previous similar observations at other ArcAcontrolled promoters (Lynch and Lin 1996b) and the finding that nonphosphorylated ArcA forms a dimer, whereas ArcA phosphorylation results in a higher oligomeric state (Jeon et al 2001).…”
Section: Figuresupporting
confidence: 80%
“…Both phosphorylated, as well as nonphosphorylated ArcA protein bound to this rpoSp1 promoter fragment, but produced different band-shift patterns (Fig. 3A), consistent with previous similar observations at other ArcAcontrolled promoters (Lynch and Lin 1996b) and the finding that nonphosphorylated ArcA forms a dimer, whereas ArcA phosphorylation results in a higher oligomeric state (Jeon et al 2001).…”
Section: Figuresupporting
confidence: 80%
“…Previous studies using electrophoretic mobility shift and DNAse I protection assays have shown that phosphorylation of ArcA is required for specific binding to target sites, that broad regions of DNA are protected by ArcA-P suggesting formation of multimers and that this multimerization can occur independently of DNA binding. 51,54,55 Solution studies, both size-exclusion chromatography and sedimentation, indicate that the isolated regulatory domain of ArcA exits exclusively as a monomer. Yet ArcA N crystallizes as a dimer in both the absence and presence of BeF 3 − .…”
Section: Arca Oligomerization and Functional Implicationsmentioning
confidence: 99%
“…51 Based on gel-filtration and glycerol gradient sedimentation analyses, Jeon et al concluded that unphosphorylated ArcA exists as a dimer and active ArcA exists as an octamer. Our SE and SV results also indicate that unphosphorylated ArcA exists as a dimer, but in equilibrium with a monomer with a K d ~400 μM.…”
Section: Arca Oligomerization and Functional Implicationsmentioning
confidence: 99%
See 2 more Smart Citations